2017
DOI: 10.1186/s40942-017-0092-9
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and functional correlation in Susac syndrome: multimodal imaging assessment

Abstract: BackgroundSusac’s syndrome (SuS) is an uncommon disease characterized by retinal microangiopathy that may be assessed more accurately with optical coherence tomography angiography (OCTA), a new imaging technique which provides a retinal microvasculature map. The purpose of this case report is to describe the multimodal imaging findings of SuS correlating OCTA with functional tests.Case presentationRetrospective review of one case with clinical and imaging evidence of SuS. Color fundus photograph, fluorescein a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Some cases of SuS analyzed by means of multimodal WF imaging 5 and OCTA [6][7][8] have been reported, but this is the first report of SuS imaged by means of WF OCTA and for an intermediate long follow-up.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Some cases of SuS analyzed by means of multimodal WF imaging 5 and OCTA [6][7][8] have been reported, but this is the first report of SuS imaged by means of WF OCTA and for an intermediate long follow-up.…”
Section: Discussionmentioning
confidence: 89%
“…4 In our case, areas of capillary non-perfusion were better outlined by WF OCTA rather than FA due to the absence of leakage and choroidal background fluorescence. Some cases of SuS analyzed by means of multimodal WF imaging 5 and OCTA [6][7][8] have been reported, but this is the first report of SuS imaged by means of WF OCTA and for an intermediate long follow-up.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, single reports have been published concerning changes in OCTA in patients with SS. These studies demonstrated an unaffected choriocapillaris vasculature and both superficial and deep retinal vascular plexuses damage characterized by vascular non-perfusion, which corresponds to the topography of BRAO [30,31]. Todorich et al described a case of SS with BRAO, where typical for BRAO hyperreflectivity of the inner and middle retinal layers was observed, characteristic of acute ischaemia [32].…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…The researchers hypothesized that a change in vascular flow associated with the activity of the disease was responsible for these changes. Inflammation of the vascular vessels may lead to a lower vascular flow due to the narrowing of the vessel [31]. Mastropasqua et al described a case of SS, where after the application of treatment, OCTA images also disclosed an increase in VD [69].…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
See 1 more Smart Citation